Flex 3 bible - Gassner, David (Wiley, 2008)
"Write programs using familiar workflows, deliver rich applications for Web or desktop, and integrate with a variety of application servers using ColdFusion, PHP, and others - all with the new Flex Builder 3 toolkit and the comprehensive tutorials in this packed reference. You'll learn the basics of Flex 3, then quickly start using MXML, ActionScript, CSS, and other tools to create applications that can run on any browser or operating system."--Jacket